Characterization of a temperature-responsive two component regulatory system from the Antarctic archaeon, Methanococcoides burtonii - Najnin, T; Siddiqui, KS; Taha; Elkaid, N; Kornfeld, G; Curmi, PMG; Cavicchioli, R (Scientific Reports, 2016)
Cold environments dominate the Earth's biosphere and the resident microorganisms play critical roles in fulfilling global biogeochemical cycles. However, only few studies have examined the molecular basis of thermosensing; an ability that microorganisms must possess in order to respond to environmental temperature and regulate cellular processes. Two component regulatory systems have been inferred to function in thermal regulation of gene expression, but biochemical studies assessing these systems in Bacteria are rare, and none have been performed in Archaea or psychrophiles. Here we examined the LtrK/LtrR two component regulatory system from the Antarctic archaeon, Methanococcoides burtonii, assessing kinase and phosphatase activities of wild-type and mutant proteins. LtrK was thermally unstable and had optimal phosphorylation activity at 10 °C (the lowest optimum activity for any psychrophilic enzyme), high activity at 0 °C and was rapidly thermally inactivated at 30 °C. These biochemical properties match well with normal environmental temperatures of M. burtonii (0-4 °C) and the temperature this psychrophile is capable of growing at in the laboratory (-2 to 28 °C). Our findings are consistent with a role for LtrK in performing phosphotransfer reactions with LtrR that could lead to temperature-dependent gene regulation.